Implementing the Circular Economy by Tracing the Sustainable Impact - Sebastian Lawrenz (MDPI AG, 2021)
Sustainability is one of the most critical issues today. Thus, the unsustainable consumption of resources, such as raw materials, CO2 emissions, and the Linear Economy needs to be changed. One framework for a more sustainable economy is the Circular Economy. Although the concept of the Circular Economy has been around since the 1990s, yet we are still far from enabling a Circular Economy. Therefore, a turnaround to the current linear economy as well as a change in society is necessary. In this paper, we get down to the essence of the status quo in the Circular Economy, identify the main barriers, such as lack of information, unsustainable economic models, ignorance, missing incentives, and propose software-driven solutions to tackle these challenges. Our solution extends the service description language by introducing the sustainability impact factor. The goal is to motivate end-users towards a more sustainable behavior without making massive restrictions on their lives.